RANCANG BANGUN SISTEM PENGELOLAAN ADMINISTRASI SEKOLAH TERINTEGRASI (SIPASTI) DENGAN PENDEKATAN PENGEMBANGAN BERTINGKAT (STUDI KASUS : SMKN ABC) - Suhendra, Suhendra; Pitaloka, Diah Mulya; Qomarudin, Heru (LPPM Politeknik Astra, 2017)
SMKN ABC is one of many public schools in Bogor, West Java. In its operation, SMKN ABC faced problems because of the data held separately and stored in each departmental section. Data and information accuration are low, often mistakes, redundant, inconsistent, slow and difficult to exchange. This study aims to provide solutions to existing problems by building an Integrated School Administration Management System (SIPASTI). SIPASTI is an intranet web-based application with three-tier architecture. The method used to develop is incremental development. With SIPASTI, SMKN ABC can produce and share information more quickly and accurately.